2009
DOI: 10.1007/s10498-009-9060-9
|View full text |Cite
|
Sign up to set email alerts
|

Uranyl Retention on Quartz—New Experimental Data and Blind Prediction Using an Existing Surface Complexation Model

Abstract: The adsorption behaviour of uranyl onto seven different samples of quartz was studied in batch experiments. Sea-sand (0.1-0.3 mm), Fil-Pro 12/20 (1-2 mm) and five Min-U-Sil samples with smaller particle sizes (5, 10, 15, 30 and 40 lm) were used. The uptake curves show ''pH adsorption edges'' in the range of pH 4-5. A good agreement of the new data with literature data was found when plotting surface-normalised distribution coefficients versus pH. Differences in the adsorption behaviour for pre-treated and untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
2
16
1
Order By: Relevance
“…The adsorption of U to quartz and silica gel is well studied in the pH range between 3 and 9, with the result that the majority of adsorption occurs at neutral pH with the specic adsorption edges/envelopes changing with surface area, U concentration, and ionic strength. [6][7][8][9] As a specic example having similar experimental conditions as our study, Huber and Lützenkirchen 9 equilibrated U solutions with 10-30 ppb U(VI) with seven different quartz samples and found that nearly all U(VI) was adsorbed at pH above 5 via surface silanol groups. Other geomaterials have been studied for their potential to immobilize soluble U(VI), such as granite, iron oxides, clays, aquifer sediments, and volcanic rock.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…The adsorption of U to quartz and silica gel is well studied in the pH range between 3 and 9, with the result that the majority of adsorption occurs at neutral pH with the specic adsorption edges/envelopes changing with surface area, U concentration, and ionic strength. [6][7][8][9] As a specic example having similar experimental conditions as our study, Huber and Lützenkirchen 9 equilibrated U solutions with 10-30 ppb U(VI) with seven different quartz samples and found that nearly all U(VI) was adsorbed at pH above 5 via surface silanol groups. Other geomaterials have been studied for their potential to immobilize soluble U(VI), such as granite, iron oxides, clays, aquifer sediments, and volcanic rock.…”
Section: Introductionsupporting
confidence: 58%
“…Deprotonated silanol groups readily adsorb metal cations and positively charged U species would be adsorbed. These results have been echoed by studies looking at U sorption to silica gels and quartz, 6,8,9 where U sorption increased with increasing pH from no adsorption at pH 2 to nearly 100% adsorption by pH 7.…”
Section: àmentioning
confidence: 93%
“…Similar formulations have been used to interpret the U isotopic composition of pore waters from deep (ca. 40 m) unsaturated zones, marine sediments and aquifers (Tricca et al, 2001;Reynolds et al, 2003;Maher et al, 2004Maher et al, , 2006Bourdon et al, 2009;Huber and Lü tzenkirchen, 2009). Variations in the pore fluid compositions of soils, and in particular semi-arid soils, have not to our knowledge been considered within this framework, although isotopic variations within the soil zone are useful for interpreting the U isotopic composition of groundwaters, rivers and secondary soil precipitates such as clays, Fe-oxides, opal and carbonate.…”
Section: Controls On ( 234 U/ 238 U) Along the Flow Pathmentioning
confidence: 99%
“…Various processes occurring in the subsurface environment (adsorption onto minerals (see e.g. (Waite et al, 1994;Duff and Amrhein, 1996;Barnett et al, 2000;Davis et al, 2004;Huber and Lü tzenkirchen, 2009)) or abiotical and microbial induced redox processes causing precipitation of sparingly soluble U phases under anoxic conditions (see e.g. (Lovley et al, 1991;Liger et al, 1999;Wall and Krumholz, 2006)) influence the migration of U leading to retardation/retention.…”
Section: Introductionmentioning
confidence: 99%